1992
DOI: 10.1111/j.1360-0443.1992.tb01905.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of smoking in Finland from 1978 to 1990

Abstract: The aim of this study was to analyse differences in smoking between men and women, and between different age groups of Finnish adults from 1978 to 1990. The data were collected by questionnaires from mail surveys of representative nationwide samples of 15-64-year-olds from 1978, annually. Response rates varied between 68% (1985) and 86% (1978), averaging 79%. Those who were less than 20 years old were excluded from this study because smoking as a habit is well-established in those aged 20 years and over. Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
(24 reference statements)
3
10
0
Order By: Relevance
“…Various studies reported a trend towards equalisation of smoking behaviour between the sexes, showing an increase in women but a decrease in men [11]. The higher rate of smokers in the low education group in our evaluation is in line with other reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Various studies reported a trend towards equalisation of smoking behaviour between the sexes, showing an increase in women but a decrease in men [11]. The higher rate of smokers in the low education group in our evaluation is in line with other reports.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, gender-differences have been described in relation to health behaviour with males exhibiting more health risks and less preventive behaviour than females [9,10]. Alcohol consumption is more common in men, but in regard to smoking a dramatic increase particularly among younger females has been reported [11]. Compared to women in other European countries, younger females in Austria show the highest rate of smoking [12].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, males exhibit more health-risk and less health-protective behaviour than females [11],[12]. However, in recent years some studies have reported a remarkable increase in smoking among women [13],[14].…”
Section: Introductionmentioning
confidence: 99%
“…We found no covariation between the birth region-specific SIRs for esophageal squamous cell carcinoma and lung cancer except for Finnish men (Table 3). Smoking prevalence was high in Finland in the early 1960s, when many Finns moved to Sweden: approximately 60% of men and approximately 15% of women smoked (Kaprio et al, 1982;Rahkonen et al, 1992;Statistics Finland, 2002) (Fig. 1).…”
Section: Discussionmentioning
confidence: 93%